(untitled) (Commonwealth Journal of Local Governance, 2022)
Fact Sheets on Decentralisation in Africa provide clear and accessible materials to assist policymakers, practitioners, students and the public at large to better understand the various concepts and mechanisms associated with decentralisation. They focus primarily on local government and unpack the ‘toolbox’ of instruments and concepts that make up the broader framework for decentralisation. These concepts are often difficult, multifaceted and located in complex theory. The aim of the Fact Sheets is to present them in such a way that they can be understood by a wide range of audiences, and which identifies, explains and distinguishes key concepts relevant to the African context.